A Miniaturized Device Based on Cobalt Oxide Nanoparticles for the Quantification of Uric Acid in Artificial and Human Sweat - Carlos D. Ruiz-Guerrero; Dulce V. Estrada-Osorio; Alejandro Gutiérrez; Fabiola I. Espinosa-Lagunes; Gabriel Luna-Barcenas; Ricardo A. Escalona-Villalpando; Luis G. Arriaga; Janet Ledesma-García (Chemosensors)
Co3O4-based materials have multiple applications in the field of materials, especially in sensor technology. In this work, Co3O4 nanoparticles were synthesized using a chemical method. The crystalline phase and crystal size were investigated by XRD, the morphology by SEM and the oxidation states by XPS techniques. The Co3O4 material was used to immobilize the urate oxidase enzyme (UOx), which showed a higher current density (1.6 times higher) than the enzyme alone in cyclic voltammetry in phosphate buffer pH 5.6. GCE/Co3O4/UOx achieved a linear range of 3.7–500 µM and a higher sensitivity of 65 µA mM−1 cm−2 compared to 45 µA mM−1 cm−2 achieved by the enzyme alone in a uric acid sensor. The favorable activity of GCE/Co3O4/UOx enabled its use in a miniaturized device with low sample volume using artificial and real human sweat. The device was used to quantify uric acid levels in five samples and showed a relative error between the calculated and expected value of less than 10%. The implementation of GCE/Co3O4/UOx is attractive in a biosensor that can be used as a uric acid sensor in biological fluids.